THE SHORT AND LONG-TERM EFFECT OF WEIGHT-BEARING MOBILIZATION-WITH-MOVEMENT (MWM) AND AUTOMOBILIZATION- MWM TECHNIQUES ON PAIN AND FUNCTIONAL STATUS IN PATIENTS WITH HIP OSTEOARTHRITIS (International Journal of Physiotherapy, 2017)
Background: There is limited evidence to support the therapeutic effect of Manual Therapy on Hip Osteoarthritis (HOA) patients. The purpose of this study was to investigate whether implementation of weight-bearing mobilization-with-movement (MWM) and auto-mobilization had a significant improvement in pain and functionality after a series of sessions.Methods: Forty patients 50-80 years of age, with HOA, were randomly assigned into two groups. Patients in the treatment group received MWM in standing position and auto-MWM for two weeks, while control patients received a Sham form of MWM. Pain and functionality were measured at baseline, post-treatment and three months’ follow-up,using the Visual Analogue Scale (VAS) and the Lower Extremity Functional Scale (LEFS). Mixed ANOVA was used to examine possible differences between treatment phases and between groups, but also interactions among Group andTime factors.Result: The present findings revealed a significant interaction between factors and significant main effects of each Time and Group factors on pain and functionality. The treatment group showed improved post-MWM VAS and LEFS scores compared to baseline scores (p